Co motywuje studentów studiów niestacjonarnych kierunku ekonomia Szkoły Głównej Gospodarstwa Wiejskiego w pracy zawodowej? - Grontkowska, Anna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
Based on the survey conducted among the group of weekends students it can be concluded that the most important motivating factor was an amount of remuneration. At the same time there was a clear difference between students expectations and the degree of their satisfaction in this area. It indicates that possibility of getting a higher salary could still motivate people and could be used as a factor increasing workers performance and productivity. Cultural changes in a society and employment policy points a shift from external motivators culture to a high tolerance of uncertainty and risk culture. An important aspect of building personnel motivation system in a future will attitude to create active behavior of employees who are flexible and open to changes. Many students pointed out higher needs of self-fulfilment, success and advancement